2008
DOI: 10.1089/ham.2007.1055
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dry Eye at High Altitude: A Case Controlled Comparative Study

Abstract: High altitude pulmonary edema (HAPE) is the leading cause of death from altitude illness and rapid descent is often considered a life-saving foundation of therapy. Nevertheless, in the remote settings where HAPE often occurs, immediate descent sometimes places the victim and rescuers at risk. We treated 11 patients (7 Nepalese, 4 foreigners) for HAPE at the Himalayan Rescue Association clinic in Pheriche, Nepal (4240 m), from March 3 to May 14, 2006. Ten were admitted and primarily treated there. Seven of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 13 publications
2
45
2
2
Order By: Relevance
“…A study from India, has reported dry eye disease to be more common in those living in high vs. low altitudes and, additionally, higher in those living at high altitudes for prolonged vs. temporary periods. The heightened exposure to ultraviolet radiation and the increase in tear evaporation during these conditions could lead to exacerbated signs and symptoms of dry eye (Gupta et al, 2008). Some of these anterior segment complications, such as pterygium (or even cataract), could have been prevented or delayed by adequate ultraviolet protection, while others, such as dry eye disease and infectious diseases, would need more involved care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from India, has reported dry eye disease to be more common in those living in high vs. low altitudes and, additionally, higher in those living at high altitudes for prolonged vs. temporary periods. The heightened exposure to ultraviolet radiation and the increase in tear evaporation during these conditions could lead to exacerbated signs and symptoms of dry eye (Gupta et al, 2008). Some of these anterior segment complications, such as pterygium (or even cataract), could have been prevented or delayed by adequate ultraviolet protection, while others, such as dry eye disease and infectious diseases, would need more involved care.…”
Section: Discussionmentioning
confidence: 99%
“…Ascents above 3,000 meters are shown to produce engorgement and tortuosity of retinal vessels and retinal haemorrhages (Rennie et al, 1975) due to hypoxia and hemoconcentration (McFadden et al, 1981), extreme physical exertion and Valsalva maneuvers (Braun et al, 1997).There is also an increase in retinal arterial and venule diameter with ascent to higher altitudes, which has been shown to return to normal upon descent (Bosch et al, 2009).Common vitreo-retinal changes for those residing at high altitudes have been reported as age-related macular degeneration, hypertensive retinopathy and retinal vein occlusion (Thapa et al, 2013). Dry eye disease has been shown to be more prevalent at high altitudes due to environmental changes leading to increased tear evaporation (Gupta et al, 2008). Effects on intraocular pressure seem inconclusive, with few studies showing a decrease 7 with ascent to higher altitudes, some showing no alteration (Clarke et al, 1976), and others showing an increase (Bayer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…UV exposure is known to increase with altitude (10 % per 1,000 m, Marín et al 2005) and is expected to be particularly high in winter due to snow cover (Dolin and Johnson 1994). Relative humidity drops with elevation (Duane et al 2008), which is considered along with sun, wind, and cold, to contribute to increased tear evaporation and dry eye syndrome in human populations living at high altitude (Gupta et al 2008), the latter being a predisposing condition for microbial keratitis (Dart 1988).…”
Section: Elevationmentioning
confidence: 99%
“…12 Dry eye disease is exacerbated in the dry, windy, and sun glare conditions seen at high altitudes. 13 Severe dry eye disease can be associated with some autoimmune disorders, and commonly-used medications can exacerbate ocular dryness. Systemic drugs with anticholinergic effects decrease tear production.…”
Section: Dry Eyementioning
confidence: 99%